2009
DOI: 10.1021/es8035972
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Aggregated C60 in the Aqueous Phase by UV Irradiation

Abstract: This study demonstrates that water-stable C60 cluster (nC60) undergoes a photochemical transformation(s) when irradiated with monochromatic UV light at 254 nm. Upon UV exposure, characteristic absorption of nC60 in the visible (ca. 450-550 nm, indicative of a cluster structure) and UV regions (indicative of underivatized molecular C60) gradually disappeared. Concurrently, a new product with absorption centered at 210 nm formed. Dynamic light scattering (DLS) and transmission electron microscopy (TEM) analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
94
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 44 publications
19
94
3
1
Order By: Relevance
“…Previous studies have demonstrated the formation of watersoluble photoproducts with oxygen-containing functional groups during the phototransformation of aqu/nC 60 [23,32]. The present study found new evidence to support this mechanism by first extracting the irradiated aqu/nC 60 with toluene, then measuring the fluorescence EEM of the water layer after the extraction.…”
Section: Resultssupporting
confidence: 73%
“…Previous studies have demonstrated the formation of watersoluble photoproducts with oxygen-containing functional groups during the phototransformation of aqu/nC 60 [23,32]. The present study found new evidence to support this mechanism by first extracting the irradiated aqu/nC 60 with toluene, then measuring the fluorescence EEM of the water layer after the extraction.…”
Section: Resultssupporting
confidence: 73%
“…Adsorption of NOM induces an increase of the degree of repulsion within the aggregate matrix and results in aggregate rupture. Additionally, UV and sunlight radiation have been shown to induce disaggregation of fullerenes (C 60 ) and the formation of soluble product (60 carbon cages containing various oxygen functional groups; Hou and Jafvert, 2008;Lee et al, 2009).…”
Section: Swcntsmentioning
confidence: 99%
“…For instance, sunlight can catalyze some redox reactions (photooxidation and photoreduction) of photoactive NMs (e.g., TiO 2 , CNTs, fullerenes) and produces reactive oxygen species when exposed to sunlight (Chen and Jafvert, 2011). Others may be oxidized or reduced by sunlight, changing their redox state, charge, and therefore aggregation state and toxicity (Hou and Jafvert, 2008;Lee et al, 2009). Sunlight has been shown to cause the degradation of gum arabic coating on AgNMs and result in enhanced aggregation and removal (sedimentation) of NMs from solution (Cheng et al, 2011).…”
Section: Swcntsmentioning
confidence: 99%
“…Degradation of C 60 in aqueous solutions through photochemical processes have been identified by numerous investigations (Sect. 3.3) (Hou and Jafvert, 2008;Lee et al, 2009;Li et al, 2009), which may be an important step in both its breakdown and the activation of pre-…”
Section: Biological Modification Of Cnms In Soilsmentioning
confidence: 99%